A configurable area-efficient LCoS chip design with centrosymmetric pixel array. (January 2023) - Zhao, Tianhu; Liang, Yuhua; Feng, Lichen
Abstract: Liquid Crystal on Silicon (LCOS) is a microdisplay technology that combines CMOS tech with integrated circuit design and liquid crystal technology. In this paper, the proposed LCOS backplane can greatly reduce size of the pixel pitch. In order to reduce the size of the pixel pitch, a digital pixel driver scheme and a new layout design are shown. The proposed LCOS with digital pixel driver scheme was fabricated using 0.18 um CMOS process technology and the simulation image have shown the correct results. The pixel size is 3 um× 6 um in this design and the area of pixel array with the resolution of 1632 × 1632 is 10127 um × 5060 um.